Dansk idræt under hagekorsets tegn - Bonde, Hans (Forum for Idræt, 2001)
Artiklen belyser idrættens rolle og betydning under anden verdenskrig med fokus på bl.a. Danmarks Idræts-Forbunds relation til besættelsesmagten. Danish Sport under the sign of the swastika On 9th April 1940 Denmark was invaded and occupied. This article deals with the response of the Danish Sports community to the German Occupation. Immediately after the German invasion the urban sports movement proved reasonably staunch in asserting the traditional apolitical status of sport in the face of German pressure. However, the wish to maintain the range and quality of Danish sport gradually became crucial to a resumption of sporting relations with Germany, which gave the occupying power considerable propaganda advantages through Danish-German international sporting events. Several rural gymnastics associations were active in the initial phases of reactionary attemps by the the world-famous Danish gymnastics leader Niels Bukh’s to create a Danish Youth League. However, there was opposition to fraternizing on football fields and other sports locations. The Danish response to fascist militarism was complex – compromise and confrontation worked side by side.